Association Of Hemoglobin Levels Among Patients with Gingivitis, Chronic & Aggressive Periodontitis - A Retrospective Study (Journal of Pharmaceutical Negative Results, 2022)
Back Ground : Periodontitis is defined as the inflammation of the supporting tissue of teeth caused by specific microorganisms or groups of specific microorganisms, resulting in progressive destruction of PDL & alveolar bone with increased probing depth formation, recession or both. Anaemia of chronic disease is defined as anemia occurring in chronic infections, inflammatory conditions, or neoplastic disorders which are not due to marrow deficiencies/ other diseases, & occurring despite the presence of adequate iron stores & vitamins.Aim : The aim of the study is to analyse the association of Hemoglobin(Hb) levels among patients with Gingivitis, Chronic & Aggressive Periodontitis.Materials And Methods : This retrospective cross-sectional study was carried out in a private dental institute which included patient’s details like Patients age, Name, Gender, periodontal status, Hb report were collected from June 2019 to March 2021. The inclusion criteria were : Patient’s name, age, gender , PID and Patient’s periodontal status, Hemoglobin level. After applying inclusion criteria, a random data of 30- Generalised chronic gingivitis patients, 30-Generalised chronic periodontitis, 30-Generalised aggressive periodontitis were collected. Datas were collected in an online forum Digital Information Archiving System and entered in Ms Excel sheet. Variables were defined and managed by entering datas to SPSS. Chi square tests and ANOVA were employed to find the association between different variables. Results: Most of the healthy patients and patients with periodontal disease commonly have Hb levels of 12-15gm/dl (53%-Healthy, 40%- Gingivitis, 73%-Chronic periodontitis, 67%-Aggressive periodontitis). All the healthy and gingivitis patients had Periodontal probing depth of 1-3mm, Major of the chronic periodontitis patients(50%) have Periodontal probing depth of >8mm and aggressive periodontitis patients (57%) have Periodontal probing depth of 57%. All the healthy and gingivitis patients have no Clinical attachment loss, 77% of the chronic periodontitis patients have Clinical attachment loss of >5mm and all the aggressive periodontitis patients have Clinical attachment loss of >5mm. The mean Hemoglobin of Generalised chronic gingivitis patients was found to be 13.36%, Generalised chronic periodontitis was found to be 13.7mg/dl and Generalised aggressive periodontitis was found to be 13.04mg/dl. On comparing, Generalised chronic gingivitis with Generalised chronic periodontitis P=0.183 and Generalised chronic gingivitis with Generalised aggressive periodontitis P=0.127. Hence, there is no significant association between Generalised chronic gingivitis with Generalised chronic periodontitis and Generalised aggressive periodontitis (P>0.05).Conclusion: The treatment of periodontitis can lead to an improvement in hematocrit and other related blood parameters in chronic generalized periodontitis patients with anemia. This provides evidence that periodontitis like other chronic diseases may also cause anemia.